Current status and development trend of carbon capture technology - Huang, Yining (Transactions on Environment, Energy and Earth Sciences, 2024)
In recent years, carbon dioxide capture (CCS) technology has garnered increasing attention as a crucial tool for addressing global climate change and air pollution. This paper delves into several carbon dioxide capture techniques, specifically pre-combustion capture, Oxy-fuel combustion capture, and post-combustion capture, and highlights the challenges encountered by each. Additionally, we have selected representative carbon dioxide capture projects from both domestic and international contexts for comprehensive analysis. Based on their specific circumstances, the anticipated future evolution of carbon dioxide capture technology is also envisioned.